Evaluation of Drug Uses for Calicivirus and Panleukopenia Treatment in Bogor Animal Clinic on 2017 and 2018 - Muhammad Agung Nulhakim; Bayu Febram Prasetyo; Rini Madyastuti Purwono (Eduvest - Journal of Universal Studies, 2021)
Drug therapy in cases of infections by viruses is only to prevent secondary infections. The use of drugs for each action must be evaluated through a drug use evaluation program (EPO) in order to guarantee a rational and effective drug. This study aims to examine the drugs in case for handling and the effectiveness of drug use in cases of infections caused by viruses, in this study the therapeutic use of drugs in cases of feline calicivirus and feline panleukopenia. This research is a descriptive study using data from 543 patients who came to get treatment of clinic in Bogor City during 2017 and 2018, 29 of which were infected with feline calicivirus and 32 infected with feline panleukopenia. Evaluation of drug use in these two viral diseases is done descriptively by comparing research data with literature. The results showed the use of drugs in the case of feline calicivirus there were 12 types of drug treatment, while in the case of feline panleukopenia there were 9 types of drug treatment. The use of drugs most often used is based on the records of veterinary clinical records, namely the preparation of metronidazole combined with cefadroxil to handle cases of feline calicivirus and metronidazole alone to handle cases of feline panleukopenia.